Revision as of 15:44, 7 October 2008 by Drmorris (Talk)

(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)

Inverse Fourier Transforms

If we have a Fourier series $ X(\omega) $, then

$ x(t)=\frac{1}{2\pi}\int_{-\infty}^{\infty}X(\omega)e^{j\omega t}d\omega $

Example

$ X(\omega)=4\pi\delta(\omega-\frac{3\pi}{2})+4\pi\delta(\omega+\frac{3\pi}{2}) $

$ x(t)=\frac{1}{2\pi}\int_{-\infty}^{\infty}4\pi\delta(\omega-\frac{3\pi}{2})e^{j\omega t}+4\pi\delta(\omega+\frac{3\pi}{2})d\omega $

$ x(t)=2\int_{-\infty}^{\infty}\delta(\omega-\frac{3\pi}{2})e^{j\omega t}+delta(\omega+\frac{3\pi}{2})d\omega $

$ x(t)=2e^{j\frac{3\pi}{2}t}+2e^{j\frac{-3\pi}{2}} $

$ x(t)=4[\frac{e^{j\frac{3\pi}{2}t}+e^{-j\frac{3\pi}{2}}}{2}] $

$ x(t)=4cos(\frac{3\pi}{2}t) $

Alumni Liaison

Correspondence Chess Grandmaster and Purdue Alumni

Prof. Dan Fleetwood